EMOTIONAL VOID AND CHILDHOOD TRAUMA: A FREUDIAN PSYCHOANALYSIS CRITICISM ON MATT HAIG'S THE MIDNIGHT LIBRARY - Prastyadi, Dini; Pandin, Moses Glorino Rumambo (Airlangga Development Journal, 2024)
Emotion is something that is always attached to every human and holds a substantial influence in affecting humans' cognitive processes. There are a lot of factors influencing the creation of emotion. One of the examples is childhood trauma. Childhood trauma can affect behavior problems such as emotion regulation. This study aims to reveal that there is a strong relationship between behavior and emotion, and childhood trauma can affect emotion in adulthood through the portrayal of the main character in Matt Haig's The Midnight Library. It is a British science-fiction fantasy novel released in August 2020. The present study applies a qualitative approach and close reading by observing the textual context of the novel. In understanding the novel, the intrinsic elements of the story, such as plot, characters, and conflict, will be analyzed. The data are analyzed by applying Freudian Psychoanalysis theory. The expected result will show that emotion in adulthood is affected by childhood trauma.